Models for employing the Foundations of Islamic Economics in Organizing Sustainable Development and Protecting the Environment - Chelli, Abdelwahab (Finance and Business Economies Review, 2022)
This research attempted to highlight the role of Islamic Sharia principles of Islamic economics in supporting the embodiment of the current model of sustainable development and environmental protection. By analyzing the relationship of some of those foundations with the requirements of embodying the legitimate environmental and developmental sustainability philosophy. As a result, he concluded that the principles of Islamic Sharia in the Islamic economy are in their infancy mechanisms that pave the way for the sustainability of the economic behavior of units in a way that supports the rationalization of consumption and production behavior and attention to environmental protection. Therefore, the specificity of the Islamic economy in its reliance on the principles of Islamic Sharia is one of the most important factors for the success of the Islamic society’s economic system in combining of development and environmental protection.